2018
DOI: 10.1002/pmh.1434
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Personality Functioning Scale‐Brief Form 2.0: Update of a brief instrument for assessing level of personality functioning

Abstract: Section III of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) introduced the alternative model of personality disorders that includes assessing levels of personality functioning. Here, we describe the development, preliminary psychometric evaluation and sensitivity to change of a revised brief self-report questionnaire, the Level of Personality Functioning Scale-Brief Form 2.0 (LPFS-BF 2.0). Patients (N = 201) referred to a specialized centre for the assessment and treatment of personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 176 publications
(211 citation statements)
references
References 40 publications
(54 reference statements)
8
153
2
11
Order By: Relevance
“…Accordingly, this structure supports previous empirical research on the DSM‐5 AMPD framework of self/other functioning . Our finding is particularly consistent with previous research on self‐reported personality dysfunction in Danish psychiatric patients and incarcerated addicts as well as Dutch psychiatric patients . Notably, in the present study we identified a correlation of.31 between the latent factors of self‐ and interpersonal functioning, which suggests that the two subdomains are somewhat entwined or inter‐dependent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, this structure supports previous empirical research on the DSM‐5 AMPD framework of self/other functioning . Our finding is particularly consistent with previous research on self‐reported personality dysfunction in Danish psychiatric patients and incarcerated addicts as well as Dutch psychiatric patients . Notably, in the present study we identified a correlation of.31 between the latent factors of self‐ and interpersonal functioning, which suggests that the two subdomains are somewhat entwined or inter‐dependent.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study warrant replication using complete and more updated self‐report measures of DSM‐5‐AMPD and ICD‐11 personality dysfunction (e.g., including features of identity disturbance). This may particularly involve the 12‐item Level of Personality Functioning Scale – Brief Form 2.0 (LPFS‐BF), the 80‐item Level of Personality Functioning Scale–Self‐Report (LPFS–SR), the 97‐item Level of Personality Functioning Questionnaire for adolescents (LoPF–Q12–18), the Level of Personality Functioning Scale – Self Report version for criterion A (LPFS‐SRA) and Observer‐Rated version for criterion A (LPFS‐ORA), and various forms of the DSM–5 Levels of Personality Functioning Questionnaire (DLOPFQ) …”
Section: Discussionmentioning
confidence: 99%
“…[309,310]). Currently, there is only a single study showing that the LPFS-BF can be used as an outcome measure in a 3month residential treatment program [31]. Fifth, one study has questioned the necessity of utilizing the complex hybrid model of the AMPD for diagnosing PDs, since applying the diagnosis of PD-TS (i.e., meeting the general PD criteria but not the criteria of not any specific type) provides full coverage of all personality pathology [311].…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of gathering self-report data, some researchers have asked participants to judge themselves according to the prototypical descriptions of the 12 subdomains [48-50]. Only recently, self-report measures building on the LPFS were newly developed, including the Level of Personality Functioning Scale-Self Report (LPFS-SR) [29], the Level of Personality Functioning Scale-Brief Form (LPFS-BF) [30,31], the DSM-5 Levels of Personality Functioning Questionnaire (DLOPFQ) [27,28], the Self and Interpersonal Functioning Scale (SIFS) [33], and the Levels of Personality Functioning Questionnaire for adolescents (LoPF-Q 12-18) [32]. For the purpose of informant ratings, it has been suggested that the 60 prototypical descriptions of the LPFS can also be rated individually by laypersons [47••, 51].…”
Section: Severitymentioning
confidence: 99%
See 1 more Smart Citation